1986
DOI: 10.1093/nar/14.21.8231
|View full text |Cite
|
Sign up to set email alerts
|

Insertion elements and transitions in cloned mouse mammary tumour virus DNA: further delineation of the poison sequences

Abstract: The provirus of mouse mammary tumour virus (MMTV) is reputed to contain sequences within the viral gag gene that prevent or inhibit its propagation as a recombinant DNA clone in Escherichia coli. Here we report the successful isolation of several lambda and plasmid clones comprising the 5' virus-host DNA junction fragments from integrated MMTV proviruses in BR6 mice. Although the lambda clones appeared intact, almost all of the plasmids were found to contain the bacterial insertion sequences IS1 or IS2 within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…We designated these viruses MMTV(C3H)hp1 and MMTV(GR)hp1. Comparison of 10 complete MMTV(C3H)hp1 and MMTV(GR)hp1 proviral sequences (minus the gag gene, which contains a poison sequence; Brookes et al, 1986) with MMTV(C3H) and MMTV(GR) sequences identified in virus preparations from murine mammary carcinoma cells, respectively, revealed that MMTV(C3H)hp1 and MMTV(GR)hp1 did not contain sequences from other viruses, the mouse genome [including endogenous mouse mammary tumour proviruses (Mtvs)] or the human genome ( Fig. S2 and data not shown).…”
Section: Persistently Infected Human Cells Produce Infectious Mmtv(c3mentioning
confidence: 99%
“…We designated these viruses MMTV(C3H)hp1 and MMTV(GR)hp1. Comparison of 10 complete MMTV(C3H)hp1 and MMTV(GR)hp1 proviral sequences (minus the gag gene, which contains a poison sequence; Brookes et al, 1986) with MMTV(C3H) and MMTV(GR) sequences identified in virus preparations from murine mammary carcinoma cells, respectively, revealed that MMTV(C3H)hp1 and MMTV(GR)hp1 did not contain sequences from other viruses, the mouse genome [including endogenous mouse mammary tumour proviruses (Mtvs)] or the human genome ( Fig. S2 and data not shown).…”
Section: Persistently Infected Human Cells Produce Infectious Mmtv(c3mentioning
confidence: 99%
“…Comparison of the 5'-end of the cDNA with genomic sequences revealed three occurrences of the pentamer (G/C)CAGT in the 52 bp of genomic sequence immediately flanking the first nt of the cDNA. The eukaryotic capsite consensus sequence TCAGT occurs in 25% of arthropod polymerase Il-transcribed promoters within 10 bp of the transcription start site (Cherbas & Cherbas, 1993). It has been suggested that this capsite consensus sequence and, less frequently, its variants (A,G,C)CAGT may be initiators (Cherbas & Cherbas, 1993).…”
Section: Cytological Location and Structure Of The White Genementioning
confidence: 99%
“…The eukaryotic capsite consensus sequence TCAGT occurs in 25% of arthropod polymerase Il-transcribed promoters within 10 bp of the transcription start site (Cherbas & Cherbas, 1993). It has been suggested that this capsite consensus sequence and, less frequently, its variants (A,G,C)CAGT may be initiators (Cherbas & Cherbas, 1993). However, the assignment of the transcription start site awaits further experiments.…”
Section: Cytological Location and Structure Of The White Genementioning
confidence: 99%
“…MMTV was the first mammalian retrovirus to be isolated. Among the retroviruses, MMTV is highly refractory to molecular studies owing to technical obstacles, which stem from two main reasons : a strong tropism to mammary alveoli cells (which are difficult to grow in cell cultures) and resistance to molecular cloning of the full-length proviral DNA [9][10][11]. This might explain why MMTV RT has not so far been expressed as a recombinant protein and why the only reports on the catalytic properties of the partly purified virus-derived RT preparations were published more than 20 years ago [12,13].…”
Section: Introductionmentioning
confidence: 99%